The Impact of the Covid-19 Pandemic on Retail Consumer Behavior - Sayyida, Sayyida; Hartini, Sri; Gunawan, Sri; Husin, Syarief Nur (APTISI Transactions on Management (ATM), 2021)
The COVID-19 pandemic that occurred throughout 2020 has an impact on economic sector. Consumers tend to use online channels to reduce face-to-face contact with marketers or other consumers. On the other hand, the consumer's need to see, touch and feel a product directly is only available in physical stores. This study aims to analyze the impact of the COVID-19 pandemic on retail consumer behavior. This study uses quantitative methods with secondary data sources obtained from several countries including the United States, England, Germany, France, Canada and Latin America. The results show that the shopping trends during the COVID-19 pandemic are webrooming and pure online shopping. Retail sales data in these countries shows that retail sales in physical stores exceed 70% of total retail sales and retail e-commerce sales are less than 30% of total retail sales. This research is expected to be useful for marketers in improving retail marketing strategies during the COVID-19 pandemic